State Responsibility of Afghanistan Under Taliban Regime - Aiyub Kadir, M. Yakub; Nurhaliza, Siti (Jurnal Media Hukum, 2000)
Serious concerns on the rights of Afghanistan’s women and girls have been raised ever since the Taliban returned to power on 15th August   2021. This paper uses a normative methodology to investigate the discrepancy of legal argument in the international law of succession in terms of status of Taliban within the Convention on the Elimination of All Forms of Discrimination Against Women (CEDAW) framework. This paper confirmed that the Taliban is the de facto government of Afghanistan as the Taliban have effective and integrated control over a state territory and there is no competing entity with a solid constitutional claim. Therefore, the Taliban is bound by international law to guarantee that women enjoy equal educational rights, including access to school and curriculum.  However, the current framework of CEDAW, including the CEDAW committee has not be able to cope with such issues, as it should be reformed in the next future.